Effect of Nigella sativa oil on various clinical and biochemical parameters of insulin resistance syndrome - Najmi, Ahmad (Medknow Publications, 2008)
AIM: The seeds of the Nigella sativa plant have been used to promote health and fight disease for centuries, especially in the Middle East and in Southeast Asia. This plant has been a focus of much research. This clinical study was undertaken to know the adjuvant effect of N. sativa oil on various clinical and biochemical parameters of the insulin resistance syndrome. MATERIALS AND METHODS: This prospective study was conducted at a tertiary health care center in North India. After confirmation of diagnosis, 60 patients who fulfilled the inclusion and exclusion criteria were enrolled in this study. Written informed consent was taken from all the patients enrolled. Approval from the institutional ethical committee was also obtained. The patients were divided into two groups of 30 each. In group I (the standard group), patients were advised tablet atorvastatin 10 mg once a day and tablet metformin 500 mg twice a day for a period of 6 weeks. In group II (the N. sativa group), the patients were advised tablet atorvastatin 10 mg once a day, tablet metformin 500 mg twice a day, and N. sativa oil 2.5 ml twice daily for a period of 6 weeks. Fasting and postprandial blood glucose, fasting lipid profile, and waist circumference were recorded before therapy and after completion of therapy. RESULT: The treatment group showed significant (P < 0.05) improvement with reference to total cholesterol, low density lipoprotein cholesterol (LDL-C), and fasting blood glucose (P < 0.05). CONCLUSION: N. sativa oil was found to be effective as an add-on therapy in patients of insulin resistance syndrome. N. sativa oil has a significant activity in diabetic and dyslipidemic patients.